공간중력모형을 이용한 목재류 수출의 결정요인 분석 - 이병훈 (한국농촌경제연구원, 2013)
The objective of this study is to account for the influencing factors of the exports of wood sector and to draw out the implication for exports strategies. This study estimated the spatial gravity model to consider spatial autocorrelation effects among export countries using spatial econometrics approaches. The empirical results of this study are as follows. The export of wood products are positively influenced by the number of Korean residents, exchange rates variables. On the other hand, the export countries' production level and distance have negative effects on the dependent variable. As additional findings, The general gravity-type model was enhanced by adding the spatial autocorrelation effect. The results of goodness of fit test confirmed the spatial gravity models are more accurate than using general gravity model.
Keywords: 공간적 효과; 공간계량경제; 공간중력모형; Spatial effect; Spatial econometrics; Spatial gravity model